Characteristics of Fresh Water Lobster Carapaces Flour (Cherax quadricarinatus). Issue 1 (1st December 2022) - Desmelati,; Suparmi,; Leksono, T
Abstract: This study aims to determine the organoletic and chemical characteristics of freshwater crayfish carapace flour. The treatment was drying in an oven at a temperature of 80°C for 24 hours. The parameters analyzed were the amount of yield, organoleptic value and proximate value. Based on the results of the study, the yield was 92.45%. The organoleptic value is based on the percentage of consumer acceptance test that likes color 98.25%, taste 95%, aroma 90%, and texture 95%, with the characteristics of bright reddish color, savory taste, not too fishy aroma, and dry and smooth texture. The chemical characteristics are: water content (4.24%), protein (15.37.%), fat (2.07%), ash (4.2%), non-nitrogen extract material 1.63% and crude fiber 19.86%. From the data From these results it can be concluded that freshwater carapace flour can be used as a fortification material in processed products.